Identification of precocious students with high Abilities/ Giftedness Indicators in the Pantanal of Mato Grosso do Sul - Martins, Barbara Amaral; Chacon, Miguel Claudio Moriel [UNESP] (Editora Univ Federal Parana, Centro Politecnico, 2023)
Students who demonstrate precocity and giftedness indicators need to be educationally encouraged to develop the potential they possess under the risk of wasting it. Recognizing the importance of the identification process to stimulate the maximum development of each one, this study aimed to identify precocious students with giftedness indicators in the language and mathematics areas, enrolled in Elementary School. It was participated of 245 students from the 1st to 5th grade of a state public school in the state of Mato Grosso do Sul, Brazil. Based on the articulation between subjective instruments (checklist for teacher nomination, self-nomination questionnaires and peer nomination) and objectives (school performance and intelligence), 12 students were identified and their parents and teachers were guided about the work with this student.
Keywords: Special Education; High ability; Giftedness; Precocity; Evaluation